2012
DOI: 10.1177/1753193412469143
|View full text |Cite
|
Sign up to set email alerts
|

Complex regional pain syndrome: observations on diagnosis, treatment and definition of a new subgroup

Abstract: Several definitions and sets of diagnostic criteria of complex regional pain syndrome have been proposed, but to date none has been accepted completely. This article presents a specific subtype of the disease, called 'chronic, refractory complex regional pain syndrome' which is extremely severe, disabling and resistant to treatment. It also emphasizes difficulties with diagnosing complex regional pain syndrome because of its variable clinical presentation and diagnostic criteria being insufficiently precise. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
0
28
0
1
Order By: Relevance
“…As observed in our case, acute CRPS may mimic various inflammatory disorders including arthritis [6]. It is relatively easy to treat when diagnosed early and has a better prognosis as compared to chronic CRPS which is more likely to result in dystonia, atrophy, and dystrophic changes [2, 3]. A fulminant acute form if not treated may progress to the chronic form within two months [2, 6].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…As observed in our case, acute CRPS may mimic various inflammatory disorders including arthritis [6]. It is relatively easy to treat when diagnosed early and has a better prognosis as compared to chronic CRPS which is more likely to result in dystonia, atrophy, and dystrophic changes [2, 3]. A fulminant acute form if not treated may progress to the chronic form within two months [2, 6].…”
Section: Discussionmentioning
confidence: 88%
“…It is relatively easy to treat when diagnosed early and has a better prognosis as compared to chronic CRPS which is more likely to result in dystonia, atrophy, and dystrophic changes [2, 3]. A fulminant acute form if not treated may progress to the chronic form within two months [2, 6]. The disease may involve the other limbs also in due course of time as seen in our patient [1].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Work has shown that different criteria may apply to Japanese patients, 5 and a new diagnostic subset of CRPS has also been proposed. 6 Increased psychiatric involvement in pain services is pertinent. Somatisation disorder is also controversial and badly diagnosed.…”
mentioning
confidence: 99%